RESPON PERTUMBUHAN BIBIT PISANG MAS (Musa acuminate Linn) TERHADAP KOMPOSISI MEDIA TANAM DAN ZPT - Ardianto, Fuad; Sutiah, Sutiah (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2017)
This research aims 1) to knowing interanction between the growing media and ZPT application to repayment bananas, 2) to knowing growing media composition best to repayment seeds banana, 3) to knowing best ZPT composition to repayment seeds bananas. This study was conducted using a randomized block design arranged in factorial (RAK). First factor that is med kind he (M) with three levels and second faktor is ZPT concentration with three levels. The variables measured covers time emerging shoots, high plant, stem diameter, number leaves, long leaf, wide leaves, number root, long roots. Analysis of data using useanalysis variance (ANOVA). The level of 5%. Result research show that no happen interaction between growing media composition and ZPT concentrationagains growth seeds bananas.